Tubulin pools in human erythrocytes: Altered distribution in hypertensive patients affects Na +, K +-ATPase activity - Amaiden, Marina Rafaela (2011)
The presence of tubulin in human erythrocytes was demonstrated using five different antibodies. Tubulin was distributed among three operationally distinguishable pools: membrane, sedimentable structure and soluble fraction. It is known that in erythrocytes from hypertensive subjects (HS), the Na +, K +-ATPase (NKA) activity is partially inhibited as compared with erythrocytes from normal subjects (NS). In erythrocytes from HS the membrane tubulin pool is increased by ∼150%. NKA was found to be forming a complex with acetylated tubulin that results in inhibition of enzymes. This complex was also increased in erythrocytes from HS. Treatment of erythrocytes from HS with nocodazol caused a decrease of acetylated tubulin in the membrane and stimulation of NKA activity, whereas taxol treatment on erythrocytes from NS had the opposite effect. These results suggest that, in erythrocytes from HS, tubulin was translocated to the membrane, where it associated with NKA with the consequent enzyme inhibition. © Springer Basel AG 2010.